Bonding as a Positive Youth Development Construct: A Conceptual Review - Tak Yan Lee; David P. P. Lok (The Scientific World Journal)
The concept of bonding as a positive youth development construct is reviewed in this paper. The goals are fourfold. First, theoretical perspectives of bonding are delineated. Secondly, the relationships among bonding to caregivers, friends, romantic partners, as well as teachers, and adolescents’ positive developmental outcomes are reviewed. Thirdly, with theoretical and empirical support, a discussion on how to promote bonding among adolescents is offered. Finally, a critical review on the cultural issues of bonding is provided.